Implementation of Community-Based Art Education Through Informal, Formal and Non-formal Education Collaborative Music Practices in Ambon City - Misye Pattipeilohy; Muhammad Jazuli; Tjetjep Rohendi Rohidi; Sunarto Sunarto (Universitas Negeri Semarang, 2022)
Abstrak. The purpose of this research is to describes the musical ecosystem in Ambon City in the form of a collab between three educational pathways, namely informal, formal and non-formal education as a form of community-based art education implementation. As one of the cities in the world that received the UNESCO Creative City of Music Award, the government and the people of Ambon City are demanded to continue to create and innovate in the development of music while maintaining the predicate as a World Music City. Implementing community-based art education is a strategy to further improve the community's musical ecosystem. This study uses qualitative research methods with data collection techniques in the form of observation, interviews, documentation and literature studies related to the object of research. The results showed that in the city of Ambon, the implementation of community-based art education already exists, but not so visible. After becoming a World Music City, there are municipal government programs through Ambon Music Office (AMO) which involves three lines of education and it has a positive impact on the local community. However, the collaboration has not been implemented widely and deeply in schools that are piloting local content curriculum based on traditional music whereas in the region there are artists and art communities that strongly support the program. If there is awareness from artists, schools and art communities who take the initiative to work together to develop music in their regions this collaboration of three educational pathways will have a major impact on Ambon City as a Music City even without the initiative of the city government. Key words: Community-Based Art Education